Atipamezole Attenuated Telazol/Xylazine-Induced Expression of C-Fos in Rat Thalamencephal and Cerebral Cortex - Bai-Shuang Yin (Sciendo, 2016)
The aim of this study was to assess whether atipamezole can restrain telazol/xylazine induced expression of c-fos in the rat brain. Rats were injected with a mixture of 13.81 mg/kg telazol and 5.21 mg/kg xylazine, following 10 min later 0.522 mg/kg atipamezole. Thereon, the thalamencephal and cerebral cortex were removed one hour after the last injection. The level of Fos protein was measured in the brain tissue by Westernblot. The results revealed that atipamezole attenuates telazol/xylazine induction of c-fos expression in the thalamencephal and cerebral cortex. The results indicated that atipamezole is able to inhibit telazol/xylazine-induced c-fos expression in the rat brain, thus protecting it from nerve damage.